POTENSI SARI LIDAH BUAYA DAN SARI LEMON DALAM MEREDUKSI FORMALIN PADA TAHU - Connie Daniela; Herla Rusmarilin; Hotnida Sinaga (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2018)
Formalin compounds that are carcinogenic, but often used as preservative tofu to extanding shelf life. This study aims to determine the effect of concentration and duration immersion of aloe vera and lemon in reducing formalin. Tofu first soaked 5% formalin then added aloe vera and lemon juices. This experiment used completely randomized design consisting of two factors, concentration of aloe vera and lemon juices, 100%:0%, 80%:20%, 60%:40%, 40%:60%, 20%:80%, 0%:100% and immersion time 30, 60, 90 (minutes) and completely nonfactorial design, treatment for storage duration 0, 3, 6, 9 (days). The parameters used are formalin test using HPLC, protein, and total microbes. The sample on storage treatment is the greatest formaldehyde reduction. Formaldehyde, protein, total microbes, of tofu 5% formalin soaked 84.214 mg/kg, 3,7939%, 1,6x104 (cfu/ml). The best treatment in decreasing formalin content is 100% aloe vera with 90 minute immersion, the remainder of formalin 28.678 ppm or 67% decreased levels of formalin in tofu, 5,5815% protein, total microbes 0, 3, 6, and 9 (days) were 7,0x104, 1,8x105, 9,3x105, and 1,5x106 (cfu/ml). Aloe vera contains saponins that act as surfactants capable of reducing formaldehyde to tofu.